Effects of gradient ambient air pollutants on wheat cultivars (HD2967 and HD3086) in vicinity of thermal power plant - Kumar, Yogesh; Mina, Usha; Kumar, Soora Naresh; Harit, Ramesh Chandra; Prakash, Pratibha; Garg, Manoj Chandra (Journal of Cereal Research, 2025)
This study involves the effects of gradient ambient air pollutants on wheat cultivars (HD2967 and HD3086) that are grown on farmersâ€™ fields located in 8 villages, namely - Jamuha, Singanpur, Parwaha, Bahadurpur, Jawaharpur, Ghasa Ka Purwa, Hajiyapur, and Murhi which are present in the vicinity of the Thermal Power Plant (TPP) at Auraiya. The present study was carried out to observe the effects of Total Suspended Particulate Matter (TSPM), Nitrogen Dioxide (NO2) and Ozone (O3) air pollutants on growth and biochemical parameters viz. - pH, relative water content (RWC), ascorbic acid (AA), total chlorophyll (TC), and yield of wheat cultivars (HD2967 and HD3086) in a 10km radius of the TPP. The wheat cultivars were grown for two consecutive years on agricultural fields in the 8 villages chosen by this study. The range of selected ambient air pollutant observed at the selected experimental site was 139-189 Âµg/m3TSPM, 23-28 ppbNO2, and 34-46 ppb O3. The dust deposition on the flag leaves of wheat cultivars was maximum (3.4 mgcm-2) in the 2-4 km area on the leeward side of the TPP while considerably lesser deposition was witnessed in the 7-9 km area on the windward side at Hajiyapur (2.5 mgcm-2). Canopy area, growth, yield attributes, chlorophyll, relative water content, and yield were significantly (P